The effectiveness and constraints of learning in polytechnic education - Gunung, I Nyoman; Darma, I Ketut (Graduate School, Universitas Negeri Yogyakarta, 2019)
This study is aimed at finding out: (1) the level of effectiveness of the teaching implementation at a polytechnic education institution viewed from the interrelatedness of the components of context, input, process, and product, and (2) the constraints in the teaching implementation at the institution. This study used the Contex Input Process Product (CIPP) model from Stufflebeam. The data were collected using a questionnaire, interview guide, and related docu-ments. The subjects of the evaluation were the students, lecturers, and the top management staff of the departments at the polytechnic. The data were analyzed using a quantitative descriptive method. The effectiveness of the learning program is determined based on the results of the prototype verification in the Glickman quadrant. The results of the analysis show that the teaching program implementation at the polytechnic viewed from the inter-relatedness of context, input, process, and product is considered effective enough. The constraints in the implementation of teaching at the polytechnic are in teaching planning, implementation of semester teaching plans, curriculum, and infrastructure as well as facilities. Those constraints create other barriers to the achievement of learning outcomes, both academic and non-academic.